Assembly of empty capsids by using baculovirus recombinants expressing human parvovirus B19 structural proteins. - Brown, C S (1991)
Empty parvovirus B19 capsids were isolated from insect cells infected with a recombinant baculovirus expressing parvovirus B19 VP2 alone and also with a double-recombinant baculovirus expressing both VP1 and VP2. That VP2 alone can assemble to form capsids is a phenomenon not previously observed in parvoviruses. The stoichiometry of the capsids containing both VP1 and VP2 was similar to that previously observed in parvovirus B19-infected cells. The capsids were similar to native capsids in size and appearance, and their antigenicity was demonstrated by immunoprecipitation and enzyme-linked immunosorbent assay with B19-specific antibodies.